Fiqih Mawaris Kontemporer: Pembagian Waris Berkeadilan Gender (TAWAZUN: Journal of Sharia Economic Law, 2018)
Justice of inheritance distribution between men and women still became actual and sustainable discussion. Various clasical views that say the distribution of inheritance between men and women is final because it is written in surat an-Nisa’ verse 11 and changing these provisions is deemed deviated from sharia, besides that, contamporary people see this as a rule that is contextualized according to the times. Progressive thinking about the distribution of inheritance was pioneered by gender activists who saw the fiqh of Mawaris still gender biased. Aim of this research was to find out the application of inheritance distribution in accordance with the conditions of Indonesian society by using a gender theory approach. The methodology used in this research is descriptive analytical by focusing on the issue of inheritance distribution 1:2 for men and women. Data analysis is carried out by reviewing the arguments about inheritance with a socio-historical approach. The results obtained from this study are the distribution of inheritance of Classical Islam 1: 2 is not something final, but can change 1: 1 or 2: 1 according to changing conditions of society. The conclusion of this research shows that to find out the purpose of Islamic law, the reader of the text of the postulate must be done contextually to get a law that is just in accordance with the objectives of Islam.